Tariff War– A Veracity with Tartness as per Indian Perspective - SOOD, DEEPAK (International Journal of Psychosocial Rehabilitation, 2020)
--- The unilateral imposition of tariff by US on various countries has started the tariff war which adversely affects the worldwide economies. This paper find that how tariff war will impact India and which sectors will highly influence by it. Few economist believes that the India’s export penetration in the US and elsewhere will increase because of China loses out. However an analysis shows that China’s export basket is more advanced and consists of more upgraded technology and finished products, India consist more of raw material and semi finished products. For this study quantitative data has been collected. This study has shown both the positive and negative impact. As per the results it impact negatively on most of the sectors in India. As the trade war will continue, therefore it is more possible that India will not get much benefits in the international market at the expense of China.